RESENHA - Constituições Brasileiras e Cidadania - Merbach de Oliveira, Samuel Antonio; Santiso, Susana Graciela; Paes de Barros e Oliveira, Joanna (Reflexão, 1999)
GALVÃO QUIRINO, Célia e MONTES, Maria Lúcia Constituições Brasileiras e Cidadania, São Paulo: Ática, 1987.